PENGEMBANGAN LKPD DIGITAL MENGGUNAKAN CANVA SEBAGAI MEDIA PEMBELAJARAN ANAK - Nabila Imtiyas Ramadhani; Ferida Rahmawati; Akbar Muhammad Farizi; Dewi Masithoh; Zidan El Zaldie (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of digital technology offers opportunities for educators to create innovative learning, one of which is through the development of digital-based Student Worksheets (LKPD). This study aims to analyze the utilization of the Canva application in developing children's LKPD and its contribution to improving the quality, creativity, and learning motivation of students in the digital era. The method used is a descriptive qualitative approach with a literature review (library research). Data were collected by reviewing various relevant literatures, such as books and scientific journals, which were then analyzed qualitatively to obtain a deeper understanding. The results indicate that Canva plays a strategic role as a fundamental solution in visualizing instructional materials and integrating multimedia in accordance with the Cognitive Theory of Multimedia Learning. The primary advantages of using Canva in LKPD include attractive and creative visual displays, increased student learning motivation, operational ease for teachers (user-friendly), and flexibility of access in hybrid learning models. However, its implementation still faces several challenges, such as dependency on an internet connection, limitations of elements in the free features, variations in teachers' digital literacy levels, and the risk of distracting students' focus toward visual aspects rather than the core content. As a practical contribution, this study formulates tactical strategies to mitigate these obstacles through sustainable digital literacy programs for teachers, the establishment of learning communities for peer mentoring, and the importance of institutional investment support in school digital infrastructure. In conclusion, with proper management and competency support, Canva serves as an effective innovative medium in transforming traditional LKPD into interactive e-LKPD to meet the demands of modern education. Keywords: Digital Technology, Children's LKPD, Canva, Innovative Learning Media.